Evaluation of internal fixation stability of distal humerus C-type fractures based on musculoskeletal dynamics: finite element analysis under dynamic loading - Zhengfeng Jia; Cheng Xu; Weilu Gao; Changsen Yang; Peifu Tang; Jiantao Li (Journal of Orthopaedic Surgery and Research)
Abstract Purpose This study establishes a quantitative anatomical-mechanical-clinical decision-making mapping relationship using the Digital Intelligence Orthopaedic Technology, systematically analyses the dynamic biomechanical characteristics of distal humerus fracture in the postoperative period, and establishes the quantitative correlation between optimal strategies of plate configuration and safety thresholds for joint activities, to provide the scientific basis for optimizing internal fixation schemes and quantifying postoperative rehabilitation strategies. Methods Upper limb muscle modeling was carried out in AnyBody software, muscle force, and other data were exported for finite distance solving and dynamic mechanical conditions were exported as the database for dynamic loading. Coupling the musculoskeletal dynamics simulation with finite element calculation, the elbow flexion-extension angle-muscle force-inner fixation stress transfer chain was established by AnyBody-Abaqus joint modeling technique to quantify the dynamic thresholds of the interface fracture micromovement (IFM) under different activity angles. The effects of different plate configurations (parallel plate, posterior medial plate, posterior lateral plate) on fracture stability and early healing were analyzed. Results In this study, we systematically evaluated the biomechanical pattern of internal fixation of distal humerus fracture as well as the postoperative safe activity window and elucidated the enhancement path of functional recovery of distal humerus fracture utilizing AnyBody musculoskeletal dynamics analysis. By means of AnyBody musculoskeletal dynamics analysis, the humerus stress migration path showed anatomical-dependent characteristics, with gradient transfer from the hawks’ fossa to the distal lateral condyle in flexion. Parallel plates stabilized the IFM in the bone healing window (0.06–0.20 mm) at 0–80° of flexion, whereas vertical plates breached the critical threshold (0.48 mm) in the IFM at > 30° of flexion. This reveals the law of mechanical matching between plate configuration and rehabilitation. There was a clear angle-dependent relationship between flexion angle and inter-fracture gap fragment motion (IFM). The IFM values tended to increase with increasing flexion and extension angles. When using parallel plates, allowing 0–80° of elbow flexion ensures better conditions for fracture healing. When using vertical plates, especially posterior medial plates active elbow flexion should be limited to about 30°. Conclusions In this study, we quantified the mechanical effect of muscle contraction force on the stability of internal fixation of distal humerus C-type fracture and revealed the biomechanical law in the postoperative period; we established a simulation model of dynamic and static loading and proposed a ‘safe activity window’ for postoperative exercise, which confirms the high stiffness of the parallel steel plate and the control of the angle of early active activity (≤ 80° of flexion). Flexion of more than 30° in the case of vertical plates leads to shear micromotion overruns (> 0.48 mm).